A pattern of serious adverse drug reactions reported in a tertiary care hospital, Rangaraya Medical College, Kakinada, Andhra Pradesh - Mendu, Sweta Bindu; Siva Prasad, K. V. (International Journal of Basic & Clinical Pharmacology, 2020)
Background: Serious adverse drug reactions (ADRs) constitute a major limitation in clinical development of a drug thus necessitating close monitoring. Studies regarding the pattern of serious ADRs are limited in southern India. The present study was conducted in tertiary care hospital in Andhra Pradesh with an objective to evaluate the pattern of severe cutaneous and non-cutaneous ADRs in our hospital and to assess the causality, severity, and preventability of these reactions. Methods: A retrospective observational study was conducted over two years, from January 2016 till January 2018 in our ADR monitoring center. The pattern of serious adverse drug reactions, the nature of ADR, suspected drug, the outcome and preventability were analyzed using Modified Hartwig and Siegel scale, and modified Schumock and Thorton scale. Results: Out of 734 ADRs reported, 42 were serious, while 692 were non-serious. Out of 42, 22 were dermatological in origin while the others were acute kidney injury, acute psychosis, febrile neutropenia, gynecomastia, and lipodystrophy. According to WHO causality assessment scale, 27 were probable while 15 were possible. The majority were reported in the age group of 16 to 65 years with female (34) preponderance. The most common drug category responsible was antimicrobials, followed by antiretrovirals, anti-epileptics, and analgesics. Conclusions: Antimicrobial, anti-epileptics, and analgesics contributed to serious ADRs. Although non-cutaneous ADRs did not result in hospitalization, they caused social inhibition and mental stress in the patient.